2019
DOI: 10.30918/aerj.73.18.076
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers' competencies in a work-based learning environment

Abstract: The study assessed and explored the pedagogical, student performance assessment, and classroom management skills of Pre-Service Teachers (PSTs) in their Work-based Learning Environment (WBLE). A sequential-explanatory mixed methods design was employed. Seventy PSTs were purposively selected as participants. To determine the three identified competencies, the study started with quantitative research method (Phase 1) using survey questionnaire containing items from various sources. After this, a qualitative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The program or curriculum for leading them in TPACK should be developed and implemented due to the course or program of study in teacher preparation program can be fulfill during the university course and school practicum. It is consistent with the Padagas [21] concept of studying the performance of the pre-service teacher in a hands-on learning environment. When considering each aspect, it was found that the pre-service teacher's classroom management competency was at the moderate level, followed by learning and teaching performance, and measurement and evaluation.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The program or curriculum for leading them in TPACK should be developed and implemented due to the course or program of study in teacher preparation program can be fulfill during the university course and school practicum. It is consistent with the Padagas [21] concept of studying the performance of the pre-service teacher in a hands-on learning environment. When considering each aspect, it was found that the pre-service teacher's classroom management competency was at the moderate level, followed by learning and teaching performance, and measurement and evaluation.…”
Section: Resultssupporting
confidence: 85%
“…Methods for enhancing learning management of the pre-service teacher is in line with the concept of Koh and Divaharan [24], they required to develop ability about technological integration expertise through the TPACK approach. It was found that reflecting learning outcomes and sharing experiences with peers will improve knowledge and use of technology in teaching and learning management as well as competencies related to TPACK by joining the community of professional learning community [21]. Also.…”
Section: Resultsmentioning
confidence: 99%
“…Then, they will also receive guidance, assistance from professional tutors, namely teachers at the schools where they practice [37]. Both supervising teachers and lecturers play essential roles in the development of teaching skill including learning rhythm, differentiation, and innovation for engaging activities [38] Practice in schools allows teacher candidates to develop abilities to communicate and ask [39], observe how teachers in schools teach and break down lesson plans with teachers and can engage with students so that they have the opportunity to work, talk, and share with students and apply what they learn in college [40]. Microteaching and direct practice in schools are suitable formulations in increasing teacher readiness because microteaching is a provision for teacher candidates to engage in practice at school [41], and it will provide an extraordinary experience for them to feel the school environment, carry out their duties and roles as teachers and behave according to the real identity of a teacher [42] such as managing class, organizing learning, and carrying out evaluation [43].…”
Section: Discussionmentioning
confidence: 99%
“…These competencies have to be acquired by teachers updating their skills and competencies on a regular basis (Yong et al, 2015). The teachers have to update their skills in classroom management, professional development (preparation of instructional documents), students' assessment skills, skills in pedagogy, skills in the human social dimension, and skills in professional ethics and morality (Padagas, 2019). When teachers possess these kinds of skills and competencies through undergoing regular professional development programmes, their service delivery level will improve, resulting in improved performance of their pupils in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, Yong et al (2015) reported that the government expected preprimary teachers to regularly improve their professional development by undertaking inservice training and attending seminars and workshops. In the Philippines, Padagas (2019) reported that there was a need for teachers to undergo professional development in order to handle the emerging demands of the field of education. The author indicated that improvement in teacher competencies through regular training would ensure the realisation of the goals and objectives of the education system.…”
Section: Introductionmentioning
confidence: 99%